IMPLEMENTATION OF GIS MADRASAH DINIYAH TAKMILIYAH (MDTA) IN ASAHAN REGENCY - Wardani, Kiki Ayu; Efendi, Bachtiar; Sumantri, Sumantri (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Madrasah Diniyah Takmiliyah as an Islamic educational institution which is under the auspices of the Ministry of Religion. The problem that has occurred so far is that it is difficult to obtain information about facilities and mapping regarding the locations of MDTA schools that are spread across Asahan, still using a manual system in providing information on MDTA schools. The purpose of this research is to build a geographic information system application that can help the community find the location of MDTA schools in Asahan District, obtain information about MDTA facilities, can assist in adding data on MDTA school locations, and update data on MDTA schools. This study uses a qualitative research method by explaining more about the analysis related to MDTA, data collection techniques through observation and documentation. Based on the research results obtained, the application of a geographic information system to determine the location of MDTA can display information and points of location of MDTA in Asahan District easily and accurately. So that it can be concluded, the geographic information system that was built can make it easier for the Ministry of Religion and the community to search for information on MDTA locations in Asahan District.            Keywords: geographic information system; madrasah diniyah takmiliyah; information system. Abstrak : Madrasah Diniyah Takmiliyah sebagai lembaga pendidikan islam yang dinaungin Kementrian Agama. Permasalahan yang terjadi selama ini sulit mendapatkan informasi mengenai fasilitas dan pemetaan mengenai lokasi sekolah MDTA yang tersebar di Asahan, masih menggunakan sistem manual dalam memberi informasi sekolah MDTA. Tujuan penelitian ini membangun aplikasi sistem informasi geografis dapat membantu masyarakat dalam mencari lokasi sekolah MDTA di Kabupaten Asahan, mendapatkan informasi mengenai fasilitas MDTA , dapat membantu dalam menambahkan data lokasi-lokasi sekolah MDTA, serta melakukan update data mengenai sekolah MDTA. Penelitian ini menggunakan metode penelitian kualitatif dengan lebih menjelaskan analisis berkaitan dengan MDTA, teknik pengumpulan data melalui observasi dan dokumentasi. Berdasarkan hasil penelitian yang diperoleh, penerapan sistem informasi geografis untuk mengetahui lokasi MDTA dapat menampilkan informasi dan titik lokasi MDTA di Kabupaten Asahan dengan mudah dan akurat. Sehingga dapat disimpulkan, sistem informasi geografis yang dibangun dapat mempermudah Kementrian Agama dan masyarakat dalam melakukan pencarian informasi lokasi MDTA di Kabupaten Asahan. Kata kunci: sistem informasi geografis; madrasah diniyah takmiliyah; sistem informasi